Multidimensional household energy poverty in rural Nigeria (2023)
The multidimensional energy poverty of rural Nigerian households was examined. The Multidimensional Energy Poverty Index (MEPI) was utilised to classify households into various energy poverty categories. Ordered logistic regression was employed to determine the factors influencing energy poverty, while multinomial logistic regression was used to assess the factors influencing energy poverty transitions. With a MEPI of 0.662, a headcount of 0.985, and an intensity of 0.668, rural households in Nigeria showed moderate levels of energy poverty. The gender and level of education, housing infrastructures, and asset value played significant roles in the multidimensional energy poverty status of rural households. Consequently, the government and other stakeholders should prioritise the formulation and adoption of diverse policies regarding the underlying factors of energy poverty. The development of human resources through a greater understanding of cleaner energy sources should also be a primary focus of development interventions. As a result of the multidimensional nature of energy deprivation, its factors and transitions may alter over time. Energy policies could be designed to target households at various levels of energy poverty. Priority should be placed on conducting additional research on appropriate intervention measures to reduce energy poverty.